Biogenic Amine Synthesis in Wheat Straw Silage with Different Additives and Varying Fermentation Days - Kabir, A.U; Abdurrahaman, S. L.; Salisu, I. B.; Dahiru, M.; Muhammad, A.S (Nigerian Journal of Animal Science, 2025)
The concentration of biogenic amines in wheat straw silage ensiled with urea (UWS), poultry litter (PLWS), watermelon peels (WPWS) and pineapple peels (PPWS) for 0, 6, 12, 18, 24, and 30 fermentation days was determined In Federal University Dutse, Jigawa state. The experiment was conducted using a factorial randomized complete block design. Wheat straw was treated with the additives an ensiled in kilner-jar. A control group sole wheat straw was also ensiled, making it 5 treatments and each treatment in triplicate. Samples were collected from each replicate and fermentation day for the analysis of biogenic amines (Histamine, Putrescine, and tyramine). The results of obtained from this study shows that the synthesis of biogenic amines increases with increase in fermentation days (P<0.05). Higher significant values were obtained in WPWS (10.23) and UWS (9.74) for histamine, while putrescine was higher in UWS (98.32) and PLWS (85.63), and tyramine was higher in WPWS (125.95) and PLWS (122.92). Conclusively, biogenic amine synthesis has a direct relationship with increase in the days of fermentation of the resultant silage.